Chest imaging for the diagnosis of complicated parapneumonic effusions. Issue 4 (July 2018) - Porcel, José M.
Abstract : Purpose of review: To provide an overview of the contribution of thoracic ultrasound (TUS) and computed tomography (CT) in the identification of complicated parapneumonic effusions (CPPE), defined as those which need chest tube drainage for resolution. Recent findings: A recent retrospective study found that visualization of complex (nonanechoic) effusions on TUS (likelihood ratio positive = 6.92) outperformed the recognition of loculated/septated effusions on CT (likelihood ratio = 2.20) or chest radiographs (likelihood ratio = 1.54) for predicting a CPPE. In another retrospective study, a weighted CT scoring system consisting of pleural contrast enhancement (three points), pleural microbubbles, increased extrapleural fat attenuation, and fluid volume at least 400 ml (one point each) had relatively good accuracy for labeling CPPE (likelihood ratio positive = 3.4; likelihood ratio negative = 0.22) when four or more points were achieved. Summary: Although a gold standard for CPPE diagnosis is lacking, bedside TUS primarily, and CT scan in certain circumstances, may help to drive clinical decisions regarding chest tube placement in parapneumonic effusions (PPE). However, recommendations are limited by the absence of prospective trials.